2015
DOI: 10.1002/ajh.24112
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the source of hematopoietic stem cell in unrelated transplants: Comparison between 10/10, 9/10‐HLAmatched donors and cord blood

Abstract: In absence of available matched-related or unrelated donor (MUD), mismatched unrelated donors (MMUD) and unrelated cord blood (UCB) are both considered to be suitable donors, with similar post-transplant overall survival. In most of these retrospective comparisons, HLA typing of adult donors was performed at eight loci. The aim of this study was to compare the outcome of patients transplanted from UCB (N 5 64) with those transplanted from 9/10-HLA MMUD (N 5 84) or 10/10-HLA MUD (N 5 196). In multivariate analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Similarly, with the exception of DR sites other than a full match or the DRB1 12: 02-12: 01 mismatch, HLA loci matching was not associated with OS in the present study. This is in agreement with previous studies that showed similar survival rates for patients undergoing matched related and unrelated, single-antigen mismatched unrelated, double cord blood [ 49 , 50 ], and haploidentical relative procedures [ 51 ]. Given the association of the natural killer cell immunoglobulin-like receptors with HLA class I ligands and patient survival and relapse [ 52 ], further studies will examine these haplotypes with GVHD occurrence in patients undergoing HSCT.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, with the exception of DR sites other than a full match or the DRB1 12: 02-12: 01 mismatch, HLA loci matching was not associated with OS in the present study. This is in agreement with previous studies that showed similar survival rates for patients undergoing matched related and unrelated, single-antigen mismatched unrelated, double cord blood [ 49 , 50 ], and haploidentical relative procedures [ 51 ]. Given the association of the natural killer cell immunoglobulin-like receptors with HLA class I ligands and patient survival and relapse [ 52 ], further studies will examine these haplotypes with GVHD occurrence in patients undergoing HSCT.…”
Section: Discussionsupporting
confidence: 93%
“…Accurately determining genotype phase is important in many aspects of genetics. For example, in pharmacogenetics 1 , transplant HLA typing 2 and disease association mapping 3 . Until recently, haplotype phasing has generally relied on parental genotypes or statistical phasing based on allele frequency patterns within the population.…”
mentioning
confidence: 99%
“…Many studies have observed higher NRM in CMV seropositive compared to seronegative recipients of UCB transplants. [22][23][24] In Brazil, the prevalence of CMV seropositivity is high. 25 We speculate that CMV could have contributed to the high mortality in these patients, since 80% of them were CMV seropositive.…”
Section: Discussionmentioning
confidence: 99%